Preoperative REM Sleep Behavior Disorder and Subthalamic Nucleus Deep Brain Stimulation Outcome in Parkinson Disease 1 Year After Surgery. (16th November 2021) - Besse-Pinot, Elsa; Pereira, Bruno; Durif, Franck; Fantini, Maria Livia; Durand, Elodie; Debilly, Bérengère; Derost, Philippe; Moreau, Caroline; Hainque, Elodie; Rouaud, Tiphaine; Eusebio, Alexandre; Benatru, Isabelle; et al.
Abstract : Background and Objectives: To determine whether patients with Parkinson disease (PD) eligible for subthalamic nucleus deep brain stimulation (STN-DBS) with probable REM sleep behavior disorder (RBD) preoperatively could be more at risk of poorer motor, nonmotor, and quality of life outcomes 12 months after surgery compared to those without RBD. Methods: We analyzed the preoperative clinical profile of 448 patients with PD from a French multicentric prospective study (PREDISTIM) according to the presence or absence of probable RBD based on the RBD Single Question and RBD Screening Questionnaire. Among the 215 patients with PD with 12 months of follow-up after STN-DBS, we compared motor, cognitive, psycho-behavioral profile, and quality of life outcomes in patients with (pre-opRBD+) or without (pre-opRBD–) probable RBD preoperatively. Results: At preoperative evaluation, pre-opRBD+ patients were older (61 ± 7.2 vs 59.5 ± 7.7 years; p = 0.02), had less motor impairment (Movement Disorder Society–sponsored version of the Unified Parkinson's Disease Rating Scale [MDS-UPDRS] III "off": 38.7 ± 16.2 vs 43.4 ± 7.1; p = 0.03) but more nonmotor symptoms on daily living activities (MDS-UPDRS I: 12.6 ± 5.5 vs 10.7 ± 5.3; p < 0.001), had more psychobehavioral manifestations (Ardouin Scale of Behavior in Parkinson's Disease total: 7.7 ± 5.1 vs 5.1 ± 0.4; p = 0.003), and had worse quality of life (Parkinson's Disease Questionnaire–39: 33 ± 12 vs 29 ± 12; p = 0.03), as compared to pre-opRBD– patients. Both pre-opRBD+ and pre-opRBD– patients had significant MDS-UPDRS IV score decrease (−37% and −33%, respectively), MDS-UPDRS III "med 'off'/stim 'on'" score decrease (−52% and −54%), and dopaminergic treatment decrease (−52% and −49%) after surgery, with no between-group difference. There was no between-group difference for cognitive and global quality of life outcomes. Conclusions: In patients with PD eligible for STN-DBS, the presence of probable RBD preoperatively is not associated with a different clinical outcome 1 year after neurosurgery. Trial Registration Information: NCT02360683. Classification of Evidence: This study provides Class II evidence that in patients with PD eligible for STN-DBS, the presence of probable RBD preoperatively is not associated with poorer outcomes 1 year post surgery.